ASSESSMENT OF SELECTED METALS ENRICHMENT IN SEDIMENTS FROM PALEA KAVALA RIVER, NE MACEDONIA, NORTHERN GREECE - Giouri, K.; Vavelidis, M.; Melfos, V.; Papadopoulou, L. (Bulletin of the Geological Society of Greece, 2016)
In surface aquatic systems, trace elements and especially heavy metals accumulate in sediments. Thus, the determination of sediment chemical characteristics is critical in the assessment of an aquatic environment’s quality. Thirteen sediment samples from Palea Kavala river (NE Macedonia, Greece) were studied for their content in Al, Fe, Cu, Cd, Mn, Pb, Zn. In order to evaluate the metal enrichment for environmental purposes, two geochemical indices were employed: Enrichment Factor (EF) and Geoaccumulation Index (Igeo). According to the results, Al was the most abundant major element in sediments with Fe and Mn to follow. Trace element content followed the order Pb>Zn>Cu>Cd. EF values revealed that samples are enriched in Cd and Pb, while Igeo values also suggested that there is considerable contamination concerning Cd and Pb. It is concluded that ore mineralizations which occur in Palea Kavala region contribute to the elevated concentrations of all the studied elements, since they comprise mainly Fe-Mn metal assemblages including minerals such as pyrite, goethite, chalcopyrite, galena, sphalerite and pyrolousite.